A Scale to Measure the Fisher’s Attitude Towards Small Scale Fisheries - Rajeshwaran M; Shivaji Argade; Ojha, S. N.; Ananthan P. S. (Journal of Indian Fisheries Association, 2021)
People’s attitude towards their livelihood activity is a priceless resource for research and development personnel to design and implement development initiatives for sustaining their livelihood. Attitude is a behavioural construct which requires standardized instrument to measure. The present study has been conducted to develop a reliable and valid scale for measuring the fisher’s attitude towards small-scale fisheries using Likert’s attitude scale construction technique. The steps include collection and editing of statements, relevancy testing of statements, statement analysis using ’t’ value calculation and standardization of the final scale using validity and reliability tests. The standardized attitude scale consists of 18 (10 positive and 8 negative) statements which were found reliable at reliability coefficient of 0.82 and satisfied content validity. The attitude scale may be useful for research and development personnel in the field of small-scale fisheries and aquaculture.